Children’s burials from the early medieval inhumation cemetery in Radom, Site 4 - Tomasz Kurasiński; Kalina Skóra (Fasciculi Archaeologiae Historicae, 2015)
The paper discusses discoveries of children’s burials from the inhumation cemetery in Radom, which was excavated in the 1960s. Data on post-mortem treatment of children from groups of infans I and infans II was discussed against the general background of burial rites in the territory of Poland in the Early Middle Ages, taking the issue of socialization of children into consideration. It was expressed by the community in funeral customs, chiefly including the problem of grave goods